The Influence of Understanding the Concept of 'Akil Baligh' and Psychological Readiness on Students' Puberty Preparation at State Islamic Junior High Schools - Asriani, Asriani; Kamaruddin, Kamaruddin; Adawiyah Pettalongi; Nur Rahma Ramadhani (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2025)
This study aims to determine the influence of understanding the concept of puberty and psychological readiness on readiness to face puberty in students. The research method used is mixed methods using the embedded design model where in this model quantitative research methods are used as primary methods and qualitative research methods are used as secondary methods. Primary data collection with a quantitative approach using the Survey research method, while secondary data collection with a qualitative approach using interview techniques. The population in this study were all students of MTs Negeri 2 Tolitoli, and samples were taken as many as 90 respondents using the quota sampling technique. The results of multiple linear regression analysis show that understanding the concept of akil balig (X1) and psychological readiness (X2) have a significant effect on readiness to face puberty (Y). The Adjusted R Square value of 0.509 shows that both independent variables are simultaneously able to explain 50.9% of the variation in students’ readiness to face puberty. Partially, understanding the concept of Akil balig has a greater influence (β = 0.596, sig. = 0.000) than psychological readiness (β = 0.250, sig. = 0.007). Qualitative findings from interviews support these results, showing that readiness to face puberty is a combination of religious understanding and emotional stability.